Sort by

- Relevance
- |Time

...e^(-1 * k)] / [e^(-2 * k) (10 / 7) = { [e^(k)]^(-1) } / { [e^(k)]^(-2) } Let e^

**k**=**c**. I chose c because it's my jam. (10 / 7) = [c^(-1)] / [c...2 Answers · Science & Mathematics · 10/06/2015

...the laws of exponents to get x's exponent in terms of

**k**: ∑ [**C**(35, k) * (-4x^6)^(35 - k) * (-2/x)^k] (from k=0 to 35) = ∑ [C(35, k) * (-4...2 Answers · Science & Mathematics · 27/11/2012

... for a, b and c, remember k is just a constant... a = 1 b = -

**k****c**= k+8 easy enough, now lets solve for x x = (k+- [sqrt(k^2-4(k+8))])/(2...4 Answers · Science & Mathematics · 14/10/2010

...http://en.wikipedia.org/wiki/Binomial_coefficient But since C(n,

**k**) =**C**(n, n-k), this is also equal to: (a + b)^n = sum over k = 0, n of C...1 Answers · Science & Mathematics · 17/10/2010

... + (-h-k)x + hk ← b = (-h-

**k**) ...**c**= hk ...1 Answers · Science & Mathematics · 17/09/2011

..., use the Binomial Probability formula: P(X =

**k**) =**C**(n, k) * p^k * q^(n-k) n : number of trials 15 k : number...1 Answers · Science & Mathematics · 10/05/2017

...where c is the constant of integration. T(t) = [r*t - r/k + H*β/

**k**+**c***exp(-k*t)] Plugging in the values for this problem: r = -2 deg/hr...1 Answers · Science & Mathematics · 28/03/2010

...where c is the constant of integration. T(t) = [r*t - r/k + H*β/

**k**+**c***exp(-k*t)] Plugging in the values for this problem: r = -2 deg/hr...1 Answers · Science & Mathematics · 29/03/2010

...a = 11 - 3c, which substituted in the second one gives you

**k**=**c**(11 - 3c), which as c varies in Z should give you all the possible ...2 Answers · Science & Mathematics · 28/02/2010

...which we could then use the Gamma identity: Gamma(1/2 + k) =√π

**k**!**C**(2k,k) / 4^k ... to come up with: √π ArcSin[√y] = ∑ (k = 0 to ∞) (1...2 Answers · Science & Mathematics · 17/01/2014